Funerary Practices of the Ancient Greek, Etruscan and Roman Civilizations: description based on the Iliad, the Aeneid and archaeological records - Valenciano, Minor Herrera (2024)
Through the study of the funerary actions of the ancient Greek, Etruscan and Roman civilizations it is possible to recognize not only the dedication and respect directed towards them, but, and perhaps most importantly, the need to honor the memory of the dead and seek with this their protection, a fact that is inherited even by other religious current, for example, Christianity. Thus, this article consists of an exposition and analysis of the funerary practices of the ancient Greek, Etruscan and Roman civilizations to determine their symbolic meaning and the importance they had for said cultures. In this way, to explain the funerary practices of these civilizations, it will be necessary to resort, when appropriate, to examples taken from Homer's Iliad, in the case of the Greeks; in the case of the Etruscans, from the existing archaeological records, and from the text of Virgil's Aeneid, in the Roman case, because they are considered literary and cultural monuments (in their etymological sense).